Implementation of Digital Leadership of Principals and Teacher in Preparing Students to Become the Golden Generation of 2045 at East Jakarta Senior High School - Silalahi, Verry Albert Jekson Mardame; Sundari, Sri; Hadiningrat, K.P. Suharyono S.; Pakpahan, Marisi (Jurnal Pendidikan, Sains Sosial, dan Agama, 2024)
Digital transformation in education is a key factor in improving the quality of learning and preparing students to face global challenges. The problem in this study is the lack of digital understanding of teachers and students. This study aims to analyze the role of school principals and teachers in the implementation of digital leadership, the implementation of education digitalization, and the results of students' digital mastery in technological development at Cahaya Sakti Jakarta Senior High School. This study uses a qualitative descriptive method. Data was obtained through in-depth interviews, observations, and documentation of school principals, teachers, and students. The results of the study show that school principals play the role of transformational leaders who drive the adoption of technology in learning. Teachers play a role as facilitators in building students' digital literacy through the use of various digital learning platforms. The implementation of digitalization of education in schools is carried out through the development of technology-based curriculum, the use of digital-based school administration systems, and the integration of technological devices in teaching and learning activities. The results of students' digital mastery showed a significant increase in critical thinking skills, creativity, and adaptation to technology. However, challenges are still faced in equitable access and understanding of technology among students and educators. The conclusion of this study confirms that effective digital leadership, adequate infrastructure support, and continuous training for teachers and students are key factors in creating a golden generation 2045 that is ready to compete in the digital era.